Technological capability and development of intellectual capital on the new technology-based firms - Acosta-Prado, Julio César; Universidad Externado de Colomabi (Pontificia Universidad Javeriana, 2014)
This article analyses the relationship between technological development and intellectual capital. Creativity and the appropriate use of knowledge are fundamental sources of technological development. They in of themselves represent the intellectual capital of companies, and lead to competitive advantage. This article argues that when technology is developed and exploited, drawing on acquired knowledge, the intellectual capital of a company is utilized and therefore enhanced. The empirical study is conducted, by the case study methodology in 35 New-Technology-Based Firms (NTBFs) at Madrid Scientific Park (PCM) and Leganés Technological Science Park (LEGATEC), located in the Community of Madrid, Spain.